(untitled) (Archives of Clinical Psychiatry, 2009)
OBJECTIVE:To understand the defenses employed by women suffering from Turner syndrome (TS) and different ways of dealing with the disease. METHOD: Qualitative research with exploratory design, non-experimental. The instrument consisted of semi-conducted psychological interview, involving 13 women, undergoing semestral medical follow-up at the Women's Health Care Center, and whose sampling was determined by saturation. Data was interpreted using the psychodynamic approach along with an eclectic framework of theoretical references for discussion in the spirit of interdisciplinary approach. RESULTS:These women displayed psychosocial conflicts such as difficulties in interpersonal relationships; feelings of resignation, anger, impotence, devaluation and depression symptoms. Defenses used were: repression, denial, annulment, fantasizing, adaptation and sublimation. DISCUSSION: Women suffering from TS or variant forms must deal with the disease's organic and psychic implications that cause great suffering and often hinder a healthier social insertion. In this case, the study's findings can guide ambulatory psychological support concomitantly to the routine clinical protocol.